Análise do efeito estrutural de variações de nucleotídeos únicos, causadores de resistência a glicocorticoides, presentes no gene codificador da proteína receptora de glicocorticoides (NR3C1). - Monteiro, Laura Lisieux dos Santos (2019)
Glucocorticoid resistance is a hereditary or sporadic condition that can affect the whole body or only certain tissues. The hypothalamic-pituitary-adrenal axis resistance to the hormone cortisol is the main pathology feature. The hereditary condition could emerge from the occurrence of variations in a single nucleotide, which could impair glucocorticoid receptor (GR) functionality. We performed computational analysis for eight variants in GR LBD domain (I559N, V571A, D641V, G679S, F737L, I747M, L753F and L773P), aiming to understand not whether but how they cause glucocorticoid resistance. The results showed that all mutations reduce the mutant GR structures stability observed by the RMSD backbone and in silico thermodynamic analysis, and binding affinity energy evaluated by the molecular docking and number of hydrogen bonds. By means of the essential dynamics analysis, we also observed changes in the movement of the receptor structure compared to the wild type, in addition to significant changes in loops of the structure evidenced by the TM-Score. In conclusion, the analyzed mutations compromise important parameters of the GR action mechanism, especially cortisol binding, translocation of the receptor-hormone complex to the nucleus and its interaction with co-activator GRIP1, characterizing the glucocorticoid resistance phenotype.